2005
DOI: 10.1007/s00125-005-1727-1
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in limb fatty acid kinetics in type 2 diabetes

Abstract: Aims/hypothesis: In order to test the hypothesis that disturbances in skeletal muscle fatty acid metabolism with type 2 diabetes are not equally present in the upper and lower limbs, we studied fatty acid kinetics simultaneously across the arm and leg of type 2 diabetic patients (n=6) and matched control subjects (n=7) for 5 h under baseline conditions and during a 4-h hyperinsulinaemiceuglycaemic clamp. Methods: Limb fatty acid kinetics was determined by means of continuous [U-13 C]palmitate infusion and meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
3
19
1
Order By: Relevance
“…Fasting whole-body fat oxidation rates were greater in the diabetes patients. This seems to be in contrast to some [14][15][16][17][18][19], but not all [12,13,36], previous studies, which describe normal and/or decreased basal whole-body fatty acid oxidation rates in the type 2 diabetic state [14][15][16][17][18][19]. These apparently contradictory findings are explained by the fact that long-term-diagnosed diabetes patients were selected to participate in the present study.…”
Section: Discussioncontrasting
confidence: 94%
“…Fasting whole-body fat oxidation rates were greater in the diabetes patients. This seems to be in contrast to some [14][15][16][17][18][19], but not all [12,13,36], previous studies, which describe normal and/or decreased basal whole-body fatty acid oxidation rates in the type 2 diabetic state [14][15][16][17][18][19]. These apparently contradictory findings are explained by the fact that long-term-diagnosed diabetes patients were selected to participate in the present study.…”
Section: Discussioncontrasting
confidence: 94%
“…53 The present findings have several implications. As previously shown by others, [18][19][20] our data indicate that muscle metabolism has a non-homogeneous distribution between arms and legs. The fact that, in other populations, arm and leg muscles are different in terms of glucose clearance 18 and also in FA kinetics, with the legs but not the arms being impaired at baseline and during a hyperinsulinemiceuglycaemic clamp, 20 is in line with our findings, in which increased fat oxidation in PO subjects was only observed during leg exercise, but not during arm exercise.…”
Section: Discussionsupporting
confidence: 85%
“…19 Furthermore, there is some evidence of heterogeneity in limb fatty acid (FA) kinetics in patients with type 2 diabetes compared with controls (C), 20 implying that arm muscle may be metabolically different from leg muscle. In a recent study, we demonstrated that maximal fat oxidation (MFO) was lower during exercise with the arms than with the legs in type 2 diabetics and in lean and O controls.…”
Section: Introductionmentioning
confidence: 99%
“…The upper and lower 13 extremities have been previously shown to be affected by type 2 diabetes to different 14 extents, with lower limbs showing a more pronounced impairment of strength and 15 greater metabolic derangement (Andersen et al, 2004;Christer . et al, 2006;Ibáñez 16 et al, 2008;Ijzerman et al, 2012;Won Park et al, 2006Olsen et al, 2005;17 Sacchetti et al, 2005). The higher neuromuscular impairment in the KE could be 18 responsible for a lower baseline muscular capacity compared to the EF and, thus, a 19 greater "gap to fill" with training.…”
Section: Patients 24mentioning
confidence: 99%